Current status and time trends of lipid and use of statins among older adults in China—real world data from primary community health institutions - Jiang, Junrong; Huang, Jun; Deng, Hai; Liao, Hongtao; Fang, Xianhong; Zhan, Xianzhang; Wu, Shulin; Xue, Yumei (Frontiers in Public Health, 2023)
Background: Elevated serum total cholesterol and low-density lipoprotein cholesterol (LDL-C) levels are established risk factors for cardiovascular diseases, a leading cause of death in China, especially in elderly population. We sought to assess the latest levels of serum lipids, prevalence of dyslipidemia and achievement of LDL-C lowering targets among Chinese elderly population. Methods: The data was obtained from the annual physical examination and medical records in primary community health institutions of Yuexiu District, Guangzhou, southern China. A sample of approximately 135,000 participants provides comprehensive estimates of the status of cholesterol level and statins use in elderly in China. Clinical characteristics were compared by different age grades, genders and years. Independent risk factors associated with statin use were determined by stepwise logistic regression analysis. Results: The mean levels of TC, HDL-C, LDL-C, TG were 5.39, 1.45, 3.10, and 1.60 mmol/L, respectively, while the prevalence of high TC, high TG, high LDL-C and low HDL-C were 21.99%, 15.52%, 13.26% and 11.92%, respectively. Although statin use showed an increasing trend in both participants ＞75 years and ≤ 75 years of age, the achievement of treatment goals fluctuated between 40.94% and 48.47%, and even seemed to have a downward trend. Stepwise multiple logistic regression analysis further indicated that age, medical insurance, ability of self-care, hypertension, stroke, CAD and high LDL-C were shown to be associated with statins use (P＜0.05). Those aged ≤ 75 years old seemed to be less likely to use statin, and those without medical insurance or ability of self-care seemed to be less likely to use statin, too. Patients with hypertension, stroke, CAD and high LDL-C were more inclined to use statins. Conclusions: Chinese elderly population currently experienced high serum lipid levels and prevalence of dyslipidemia. Although an increasing trend was showed in the proportion of high CVD risk and statin use, the achievement of treatment goals seemed to have a downward trend. Improvement of lipid management is necessary in order to reduce the burden of ASCVD in China.